PEMBELAJARAN KONSEP WAKTU BERBASIS MATEMATIKA REALISTIK DENGAN PERMAINAN GASING SISWA KELAS II SD - Rahmadani, Salma Aulia; Febrianti, Siska Nadia; Natasya, Syaharani Naswa; Zuliana, Eka (LPPM Universitas Muhammadiyah Bulukumba, 2025)
Education is the main foundation in shaping a generation that is competent and adaptive to the times. One of the important aspects of basic education is learning mathematics, especially on the subject of time measurement. The concept of time is often a challenge for students because of its abstract nature. Therefore, this study aims to develop an effective learning strategy through the Indonesian Realistic Mathematics Learning (PMRI) approach supported by concrete media, such as the Time Board and the spinning top game. This research used descriptive qualitative method with data collection techniques in the form of observation, documentation, limited interviews, and concept understanding tests. The research subjects were grade II students of SDN 4 Karangbener with a total of 27 students. The results showed that the use of the Time Board media helped students understand the concept of time better, while the top game increased their learning engagement and motivation. However, there was a difference in time measurement results between students who calculated orally and those who used analog clocks, indicating the need for further practice in reading clocks and measuring time duration accurately. This research shows that experiential learning is more effective than traditional methods. With a more applicable and fun approach, students are expected to not only understand the concept of time theoretically but also be able to apply it in everyday life.